2009
DOI: 10.1007/s10668-008-9183-y
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors on sustainable development: a case study in Quang Tri province, Vietnam

Abstract: Background Sustainable development (SD) is a common concept. Knowledge and attitudes are essential in the SD process. This study assesses the knowledge, attitudes, and practices (KAP) of local people about SD. Aim To study the factors that influence the understanding of the concept, contents, and indicators of different aspects affecting the health and environmental issues. Methods A cross-sectional study was carried out from June to July 2007 among 546 households in the Quang Tri province. Data were gathered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The evaluation of these psychometric properties contrasts with the absence of validations that are frequently observed in KAP studies on sustainability. Besar et al (2013), Kioko et al (2010) and Hai et al (2010) did not describe where the items were obtained and did not account for the validation of the instruments. In the study of Johar and Razak (2015), the items were extracted from other works, and the validation of the instrument was not accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of these psychometric properties contrasts with the absence of validations that are frequently observed in KAP studies on sustainability. Besar et al (2013), Kioko et al (2010) and Hai et al (2010) did not describe where the items were obtained and did not account for the validation of the instruments. In the study of Johar and Razak (2015), the items were extracted from other works, and the validation of the instrument was not accounted for.…”
Section: Discussionmentioning
confidence: 99%
“…The practices described in the studies are consistent with the attitudes found in them. Mansaray et al (1998), Hai et al (2010), Johar and Razak (2015) and Fernández-Manzanal et al (2015) reported low scores in sustainability practices and/or low participation in environmental activities, as well as found negative attitudes or a low disposition and willingness to participate. Kioko and Kiringe (2010), Mlipha and Manyatsi (2005) and Da Silva (2015) found positive attitudes, or high scores, for sustainability practices such as a high participation in environmental activities, including the incorporation of sustainability and tree planting.…”
Section: Practices Related To Sustainabilitymentioning
confidence: 98%
“…These are only few of the examples of ‘different’ mental models that contributed to the development of the systems model and on which the on‐going success of the Cat Ba project will be dependent. A recent case study in central Vietnam (Hai et al ., ) shows that local people have little knowledge about sustainability, most of them do not understand sustainable development in general, and they do not want to participate in sustainable development programmes. It is therefore not surprising that the attitude of local people in Cat Ba is no different.…”
Section: Systems Thinkingmentioning
confidence: 99%